2014
DOI: 10.1111/jpy.12175
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Gambierdiscus scabrosus sp. nov. (Gonyaulacales): a new epiphytic toxic dinoflagellate from coastal areas of Japan

Abstract: A new epiphytic dinoflagellate is described, G ambierdiscus scabrosus sp. nov., from tidal pools and rocky shores along the coastal areas of Japan. Cells are 63.2 ± 5.7 μm in depth, 58.2 ± 5.7 μm in width, and 37.3 ± 3.5 μm in length. The plate formula of G . scabrosus is Po, 4', 0a, 6'', 6c, ?s, 5''', 0p, and 2''''. Morphologically, G . scabrosus resembles G . belizeanus as follows: anterioposteriorly compressed cell shape, narrow 2'''' plate, and areolated surface. Despite this similarity, the cells of G . s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 25 publications
(66 reference statements)
5
83
0
Order By: Relevance
“…Likewise, it is presently still debated whether the severity of the illness is solely influenced by the dosage of toxin ingested and/or the toxin type or whether toxins produced by co-occurring dinoflagellates, such as species of Prorocentrum, Coolia, and Ostreopsis (Figure 1(b)e(d)) (Nishimura et al, 2014) influence severity and symptomology (Lewis, 2006;Tosteson et al, 1988). Regardless, ciguatera induced more intense research in areas with endemic ciguatera, and this has revealed that the genus Gambierdiscus is more complex than previously assumed.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Likewise, it is presently still debated whether the severity of the illness is solely influenced by the dosage of toxin ingested and/or the toxin type or whether toxins produced by co-occurring dinoflagellates, such as species of Prorocentrum, Coolia, and Ostreopsis (Figure 1(b)e(d)) (Nishimura et al, 2014) influence severity and symptomology (Lewis, 2006;Tosteson et al, 1988). Regardless, ciguatera induced more intense research in areas with endemic ciguatera, and this has revealed that the genus Gambierdiscus is more complex than previously assumed.…”
Section: Introductionmentioning
confidence: 97%
“…The regions where the thecal plates overlap (the sutures) gives rise to a complex pattern of plate arrangements called tabulation, which is used to distinguish genera and species of armored dinoflagellates (Nishimura et al, 2014 and references therein). For species of the genus Gambierdiscus, however, differences in tabulation are very subtle, so that light-and scanning-electron microscopy alone is insufficient for unequivocal identification (Murray et al, 2014;Nishimura et al, 2014). Cells of Gambierdiscus are typically photosynthetic, anteriorly/posteriorly compressed and lentil to ellipsoid in shape (except for G. ruetzleri and G. yasumotoi, where the cells are globular (Litaker et al, 2009)) containing a dorsally located u-shaped nucleus (Nishimura et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some preliminary data about species-specific Gambierdiscus toxicity have been obtained by a new, rapid extraction procedure, which facilitates the simultaneous detection of the lipid-soluble CTX and the water-soluble maitotoxin (MTX) fractions obtained from Gambierdiscus extracts and validated by liquid chromatography mass spectrometry (LC/MS) and functional bioassay (Lewis et al, 2016). Based on the combination of these and other methods, CTX and MTX have been clearly detected in G. polynesiensis and G. scabrosus in the Pacific, and G. excentricus in the Caribbean/Atlantic; these species would likely pose the main concerns for toxin transfer into the marine food webs where detected (Chinain et al, 2010a;Fraga et al, 2011;Nishimura et al, 2014;Rhodes et al, 2014).…”
Section: Improved and Reliable Detection Of Toxins In Ostreopsis And mentioning
confidence: 99%
“…Screening of samples from divergent locations with these assays has provided new insights into the biogeography of these species (e.g., some are endemic to the tropical Pacific or Caribbean while others are more widely distributed). Since then, six additional species have been newly described: G. excentricus and G. silvae from the Canary Islands (Fraga et al, 2011;Fraga and Rodríguez, 2014); G. scabrosus from Japanese coastal waters (Nishimura et al, 2014); G. balechii discovered in the Celebes Island (Fraga et al, 2016; see opening page photo b); G. cheloniae from the Cook Islands , and G. lapillus in Great Barrier Reef waters (Kretzschmar et al, 2017). The Gambierdiscus cf.…”
Section: Improving Taxonomy To Identify Organismsmentioning
confidence: 99%